New record of species parema Sulcata (Krieger) 1906 (Hymenoptera:Ichneumonidae: Pimplinae) from Indonesia - Amanda , T.P.O.; Yaakop , S.; Idris , A.B. (Pusat Sistematik Serangga ,UKM, 2013)

(untitled)
A new record of the species Parema sulcata (Krieger) 1906 (Hymenoptera: Ichneumonidae: Pimplinae) from Irian Jaya, Indonesia is reported. This species was reported for the first time and described by Krieger in 1906 and only encountered in Philippines with the name Theronia sulcata Krieger, 1906. Gupta (1962, 1987) redescribed the species Theronia sulcata Krieger, 1906 and discovered a new genus and subspecies-Parema sulcata sulcata Krieger and Parema sulcata ferrugata Gupta. However, he only relied on the colour characters in determining the difference between both subspecies. We synonymized the subspecies described by Gupta (1962) as we believe that colour is not a strong character for defining subspecies level. The species Parema sulcata Krieger was redescribed following a trip to `Lembaga Ilmu Pengetahun Indonesia' (LIPI) Bogor, Indonesia.